The Impact of Stone Quarrying on Socio Economic Status of Households in Nyakyibigi Ntungamo Municipality. - Natweeta, Elvason (Kabale University, 2023)
The study assessed the impact of stone quarrying on socio economic status of households in Nyakyibigi Ntungamo municipality. The objectives of the study were; to investigate the technologies used in stone quarrying in Nyakyibigi, Ntungamo municipality, to find out the effects of stone quarrying activities in Nyakyibigi Ntungamo municipality and to identify strategies to curtail the problems faced by people resulting from stone quarrying in Nyakyibigi Ntungamo municipality. A descriptive research design was used and a sample size of 80 respondents was used for the study. The study findings on the technologies used in stone quarrying in Nyakyibigi, Ntungamo municipality were; blasting technology, the use of sawing, drilling technology and splitting techniques. The study findings on effects of stone quarrying activities in Nyakyibigi Ntungamo municipality were; increased businesses, increase in transport services, land became more valuable, increased demand of agricultural products, increased employment in the area and development of services like electricity. The study findings on strategies to curtail the problems faced by people resulting from stone quarrying in Nyakyibigi Ntungamo municipality were; provision of tax holidays to investors, strengthening of security in quarrying areas, importing equipment's to use in quarrying process and rehabilitation of roads. The study recommended there should be strengthening of security in quarrying areas in order to protect the quarrying activities which leads to improvement at the quarrying site, there should be carefully pre-planning of the project to ensure that the quarrying process takes place well and in its actual state because when this one is done, then the activity also goes on well to facilitate the desires of the community and there should be fitting of drills with dust collection systems and purchasing additional land surrounding the mine to act as a buffer zone and trees planted in these buffer zones can also minimize the visual impact of quarrying operations on local communities.